Recombination occurs within minutes of replication blockage by RTS1 producing restarted forks that are prone to collapse - Michael O Nguyen; Manisha Jalan; Carl A Morrow; Fekret Osman; Matthew C Whitby (eLife, 2015)
The completion of genome duplication during the cell cycle is threatened by the presence of replication fork barriers (RFBs). Following collision with a RFB, replication proteins can dissociate from the stalled fork (fork collapse) rendering it incapable of further DNA synthesis unless recombination intervenes to restart replication. We use time-lapse microscopy and genetic assays to show that recombination is initiated within ∼10 min of replication fork blockage at a site-specific barrier in fission yeast, leading to a restarted fork within ∼60 min, which is only prevented/curtailed by the arrival of the opposing replication fork. The restarted fork is susceptible to further collapse causing hyper-recombination downstream of the barrier. Surprisingly, in our system fork restart is unnecessary for maintaining cell viability. Seemingly, the risk of failing to complete replication prior to mitosis is sufficient to warrant the induction of recombination even though it can cause deleterious genetic change.